Why Mental Disorders are not Like Software Bugs. Issue 4 (11th October 2022) - Fagerberg, Harriet
Abstract: According to the Argument for Autonomous Mental Disorder (AAMD), mental disorder can occur in the absence of brain disorder, just as software problems can occur in the absence of hardware problems in a computer. This article argues that the AAMD is unsound. I begin by introducing the "natural dysfunction analysis" of disorder, before outlining the AAMD. I then analyze the necessary conditions for realizer autonomous dysfunction. Building on this, I show that software functions disassociate from hardware functions in a way that mental functions do not disassociate from brain functions. It follows that mental disorders are brain disorders necessarily.